The Opinions of Teaching Staff in the Faculty of Education at University Tishreen About the Reality of Educational Researches and its Activation ways - Field study - Melaad , Mahmoud; Ksheek , Muna; Ali , Abeer (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
. The Research aimed to identify the Opinions of Teaching Staff in the Faculty of Education at Tishreen University About the Reality of Educational Researches (importance, realization, and its activation ways). and to define the differences in this Opinions according to these variables (department, academic rank, and, experience). To achieve the objectives of the research, was applied questionnaire prepared for this purpose, consisted (52) items, which distributed for three axis (importance, realization, and its activation ways), questionnaire has been applied on sample (104) members during the academic year of (2015 - 2016). Validity and the reliability was established. The results showed that the importance of educational researches were a higher degree among teaching staff members in the faculty of education at Tishreen University, also the Reality of educational researches were a middle degree, in addition to, results showed that the activation ways were a higher degree. In fact, there aren’t statistically significant differences about importance, realization, and its activation ways due to the (department, academic rank, and, experience). Finally, the research suggested that Researcher be acquainted with the educational research and encouraged by granting them financial and moral incentives. Moreover, researches persistently training courses on the methods of conducting research.